Production of A2 0 and ω* (1675) in the reaction π-p → π+π-π0n at 12 and 15 GeV/c - Corden, M; Dowell, J; Garvey, J; Jobes, M; Kenyon, I; Mawson, J; McMahon, T; Corbett, I; Esterling, R; Lipman, N; Litchfield, P; Sumorok, K; et al. (1978)
Data on the reaction π-p → π+π-π0 have been taken at 12 and 15 GeV/c with the CERN Omega multiparticle spectrometer. In a 3-pion partial-wave analysis strong production of A20 (1310) and ω* (1675) is observed. Total and differential cross sections are determined and density matrix elements presented as a function of t in the t- and s-channel frames. The energy dependence of A20 production is studied, and a comparison of ω(780), A20(1310) and ω* (1675) production is made. © 1978.